Investigation of the strength and toughness of FRHPC after exposure to high temperature - Yining Ding (2008)
The investigations on different fibre influences on the compressive strength, the flexural strength and ductility as well as failure pattern of fiber reinforced high-performance concrete (FRHPC) after exposure to various high temperature were carried out. The results indicated that the compressive strength of HPC without fibres declined strongly after high temperature at 900oC, the residual compressive strength was only 10% compared to the original strength. However, both steel fiber (SF) and polypropylene (PP) fiber can reduce the negative effect of high temperature on the strength. The micro PP fiber can mitigate the surface spalling of HPC member significantly, but did not show clear effect on the flexural toughness of concrete matrix. In contrary, the HPC reinforced with macro steel fiber illustrated higher flexural toughness and ultimate load bearing capacity before and after high exposure temperatures. The mechanical properties of HPC reinforced with fibre cocktail (SF + PP) were better than that of HPC reinforced with mono-fibre. Besides, the failure mode of FRHPC beams changed from pull-out of steel fibers at lower temperature to tensile failure of steel fibers at higher temperature (900 oC).